2018
DOI: 10.1590/s0004-2803.201800000-35
|View full text |Cite
|
Sign up to set email alerts
|

Serum Infliximab Measurement in Inflammatory Bowel Disease Patients in Remission: A Comparative Analysis of Two Different Methods in a Multicentric Brazilian Cohort

Abstract: BACKGROUND: Infliximab (IFX) therapeutic drug monitoring is an important tool to guide therapeutic decision in inflammatory bowel disease patients. Currently, there are two methods to measure trough levels of IFX, ELISA assays or rapid tests. Despite that the ELISA assay is the most used method in therapeutic drug monitoring, the results take long to be available for clinical use, and it needs to be performed by trained personnel. In contrary, the results of a rapid test take 20 to 30 minutes to be available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Similar supra-therapeutic levels were found by Parra et al (11.3%) in a study using the Quantum Blue rapid test (5). In another multicentric study, similar proportions were also found (8.16% with a different ELISA assay and 16.33% with the Quantum Blue rapid test) (6). The percentage of supra-therapeutic levels found by Gomes et al (80% of the sample), even considering the upper limit of 10 µg/mL, is extremely high and not compatible with other studies from the same country.…”
supporting
confidence: 53%
“…Similar supra-therapeutic levels were found by Parra et al (11.3%) in a study using the Quantum Blue rapid test (5). In another multicentric study, similar proportions were also found (8.16% with a different ELISA assay and 16.33% with the Quantum Blue rapid test) (6). The percentage of supra-therapeutic levels found by Gomes et al (80% of the sample), even considering the upper limit of 10 µg/mL, is extremely high and not compatible with other studies from the same country.…”
supporting
confidence: 53%
“…Regarding point-of-care tests, two types were widely studied, namely, Quantum Blue and lateral flow assay. Both showed a good correlation with ELISA in seven observational studies 27 28 30 31 35 39 41. In one study, both point-of-care methods are compared with each other and demonstrate good correlation 41…”
Section: Resultsmentioning
confidence: 98%
“…Several assay formats are available to measure biopharmaceutical blood concentrations, of which ELISA is the most widely used. In total, 20 studies were identified that compared two or more formats for biopharmaceutical blood concentration measurement 23–42. In 12 studies, agreement between different assay formats and ELISA formats was investigated 23–27 29 34 36 37 40–42.…”
Section: Resultsmentioning
confidence: 99%
“…However, Kampa et al themselves admitted that the limitations of their paper were its retrospective character (failures in data collection might occur) and the absence of a detailed description of the clinical and endoscopic conditions at the moment of collection. Additionally, the aim of Teixeira et al 4 was to measure the serum levels of IFX by comparing two different, already validated, assays 6,7. Although this approach was indeed interesting, the majority of patients included in the study (88%) were in remission, a condition that is not impacted by therapeutic drug monitoring in clinical practice.…”
mentioning
confidence: 99%
“…Although this approach was indeed interesting, the majority of patients included in the study (88%) were in remission, a condition that is not impacted by therapeutic drug monitoring in clinical practice. Teixeira et al 4 even suggested that more studies on patients with active disease would be necessary. Finally, Parra et al 5 evaluated the levels of IFX in a larger cohort of 55 patients with CD and 16 with UC.…”
mentioning
confidence: 99%